If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1q + 13 = -4 Reorder the terms: 13 + 1q = -4 Solving 13 + 1q = -4 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 1q = -4 + -13 Combine like terms: 13 + -13 = 0 0 + 1q = -4 + -13 1q = -4 + -13 Combine like terms: -4 + -13 = -17 1q = -17 Divide each side by '1'. q = -17 Simplifying q = -17
| F(x)=2x^2+3x-9 | | 5y+7=3y-21 | | 7h+4=54 | | 4x-6-6x+10=12 | | 6k+1=19 | | D-126=98 | | 0.4x+5.4=4.8 | | -2x-y-3z=12 | | 6(4s+7)=330 | | X^2-16X-936=0 | | (8/12)/2 | | 3.7(-83x-3)=307(7x-30) | | x^2+9=-12 | | 2x+3y+4z=18 | | 2/3/4=x6 | | 124=200-4s | | 4r^2-17r+12=0 | | (d/3)-8=-24 | | 2m-[m+6]=4[m-3] | | x^2+3x=x^2-2x | | 5x-30=65 | | 72=18k | | d/3-8=-24 | | X/5=95 | | (5/2)/50=x/80 | | 19g=133 | | 4-0.3p=0.2p-2 | | 500-6s=116 | | 51x53/53 | | 2x-18=146 | | 2ab-4b^2+2= | | F(x)=-3x-p |